2014
DOI: 10.3109/07420528.2014.957297
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of supplemental work from home in the European Union

Abstract: Internationalization and technological developments have changed the work organization in developed and developing industrial economies. Information and communication technologies, such as computers and smartphones, are increasingly used, allowing more temporal and spatial flexibility of work. This may lead to an increase in supplemental work, i.e. constant availability or working in addition to contractually agreed work hours. This in turn extends work hours and leads to work hours in evenings and weekends, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 21 publications
0
45
0
3
Order By: Relevance
“…Although it was a plausible expectation, past research has not shown a bivariate relationship between workplace telepressure and presenteeism, referring to engaging in work-related activities while being ill (Koopman et al, 2002). This was surprising because research has demonstrated that constant exposure to work-related tasks via technological devices may be linked to physical health problems in the long run (Arlinghaus & Nachreiner, 2014;Lanaj, Johnson, & Barnes, 2014). Therefore, this study aimed to replicate the bivariate relationships between workplace telepressure and physical and psychological health outcomes.…”
Section: Workplace Telepressure and Health Outcomesmentioning
confidence: 91%
“…Although it was a plausible expectation, past research has not shown a bivariate relationship between workplace telepressure and presenteeism, referring to engaging in work-related activities while being ill (Koopman et al, 2002). This was surprising because research has demonstrated that constant exposure to work-related tasks via technological devices may be linked to physical health problems in the long run (Arlinghaus & Nachreiner, 2014;Lanaj, Johnson, & Barnes, 2014). Therefore, this study aimed to replicate the bivariate relationships between workplace telepressure and physical and psychological health outcomes.…”
Section: Workplace Telepressure and Health Outcomesmentioning
confidence: 91%
“…Therefore, controlling working hours is essential. 16 A study conducted in China discussed how the sudden suspension of classes and compulsory home quarantine made home the only place where education could take place. 14 This unplanned change does not allow time for psychological preparation, and since most faculty members live with their families, interference by other family members might interrupt the completion of certain tasks at home.…”
Section: Discussionmentioning
confidence: 99%
“…In higher-TSD cultures, by contrast, time use is more fluid. Employees in information-based industries may continue to work after the end of normal business hours (Arlinghaus & Nachreiner, 2014).…”
Section: Individual-level Tsd: Implicitmentioning
confidence: 99%